Formulation of Nutraceutical Dosage Form Cempedak Leaves (Artocarpus integer (Thunb.) Merr) Cereal as Immunity Booster for Children - Esadini, Aya Rana; Aulia, Gina; Fu’adah, Intan Tsamrotul (Jurnal Kefarmasian Indonesia, 2024)
Cempedak (Artacorpus integer (Thunb.) Merr) is a plant whose fruit is commonly consumed by the public. However, the leaves are still not widely used and have been reported to have various benefits as efficacious herbal medicines. This is due to its phenolic compounds which play a role in counteracting free radicals and indirectly positively impact the body's immunity. This study aims to formulate cempedak leaf cereal as a new nutraceutical for children. The stages carried out include making extracts, cereal formulations, and evaluating the characteristics of cempedak leaves cereal including organoleptic, specific gravity, compressibility index, flow rate, granule repose angle, moisture content, reconstitution time, organoleptic and pH tests after reconstitution, sedimentation volume, and physical stability test. The formulations were three variations, namely F1 (containing 1% extract), F2 (containing 3% extract), and F3 (containing 5% extract) in the form of granules using wet granulation methods. The formulation and evaluation results of the three formulations are not much different from one another. However, based on the results of the compressibility index, F2 met the good standard criteria, namely 9.23%. The aroma and taste of the formulation are the same as commercial cereals, so we are sure that children will like them. In addition, the results of phytochemical tests also showed that the secondary metabolites contained in cempedak leaf extract could act as immune boosters. The three formulations also showed good stability for 30 days. Based on the results, our formulation met the criteria as nutraceuticals.